TENDENCIES OF INDUSTRIAL DEVELOPMENT IN NAMANGAN REGION - Ibrogimov Sherzodbek Halimjon ogli (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article discusses the development of the industrial sector of the Namangan region. And also analyzed the economic trends in this sector.